Household decision making in rural china: Using experiments to estimate the influences of spouses - Fredrik Carlsson; Haoran He; Peter Martinsson; Ping Qin; Matthias Sutter (Institute for the Study of Labor (IZA), 2010)
Many economic decisions are made jointly within households. This raises the question about spouses' relative influence on joint decisions and the determinants of relative influence. Using a controlled experiment (on inter-temporal choice), we let each spouse first make individual decisions and then make joint decisions with the other spouse. We use a random parameter probit model to measure the relative influence of spouses on joint decisions. In general, husbands have a stronger influence than wives. However, in richer households and when the wife is older than the husband, we find a significantly stronger influence of the wife on joint decisions.
urn:nbn:de:101:1-201010132822
Keywords: C91; C92; C93; D10; 330; household decision making; spouses; relative influence; random parameter model; field experiment; time preferences